PENGARUH JOB ENLARGEMENT DAN KELELAHAN EMOSIONAL TERHADAP KEPUASAN KERJA PETUGAS PEMADAM KEBAKARAN KABUPATEN SIDOARJO - Dimas Rangga Dewantara; Ika Korika Swasti (JURNAL LENTERA BISNIS, 2025)
This research aims to analyze the influence of job enlargement and emotional exhaustion on the job satisfaction of firefighters in Sidoarjo Regency. The background of this study is based on the phenomenon of increasing absenteeism in recent years, the burden of job enlargement, and the emotional pressure experienced by firefighters in carrying out their operational and non-operational duties. This study used a quantitative approach with a sample of 42 officers selected through purposive sampling. Data were obtained using a questionnaire and analyzed statistically using the Structural Equation Modeling (SEM) method assisted by SmartPLS 3.0 software. The results found that job enlargement and emotional exhaustion partially had a significant negative effect on job satisfaction. These findings indicate that increasingly varied tasks in high-risk jobs can reduce job satisfaction levels. Additionally, high emotional stress in the workplace caused by working conditions also contributes to a decrease in staff satisfaction.